Updating the knowledge of species of the genus Astylus Laporte (Coleoptera: Melyridae) from South America - Estrada, Patricia (Zootaxa, 2021)
Pic has contributed most of the descriptions of species and varieties of the genus Astylus Laporte, 1836. However, in some cases, he defined the distinction between taxa on the basis of variable characters. The study of the external morphology and genitalia of the type material of Astylus alboscutellatus Pic,1919a; A. banghaasi Pic, 1902; A. banghaasi var. reichei Pic, 1919a; A. binotatus Pic, 1940; A. elongatior Pic, 1902; A. elongatior var. disjunctus Pic, 1902; A. scalaris Pic, 1919b and A. tucumanensis Pic, 1902, as well collections material, allows to establish new diagnoses and new nomenclatural changes. Following new synonymies are proposed: A. banghaasi Pic, 1902 (= A. banghaasi var. reichei Pic, 1919a n.syn. = A. elongatior Pic, 1902 n.syn. = A. elongatior var. disjunctus Pic, 1902 n.syn.) and A. scalaris Pic, 1919b (= A. binotatus Pic, 1940 n.syn.). The valid species are redescribed.